Implementasi Kurikulum Merdeka dalam Mata Pelajaran Bahasa Inggris di MI Al-Mahad An-Nur Yogyakarta - Minati Rina Hardiyana; Sabarudin Sabarudin; Lina Lina; Siti Maryam (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The implementation of the independent curriculum at MI Al-Mahad An-Nur has been running for one year. Therefore, this study aims to determine the implementation of the independent curriculum in English subjects at MI Al-Mahad An-Nur. This research uses a descriptive qualitative research type. Data were obtained through interviews, observations, and documentation. The data were then analyzed through data collection, data condensation, data presentation, and conclusions. Based on the research results, the implementation of the independent curriculum in English language learning at MI Al-Mahad An-Nur has been carried out well. The teachers at MI Al-Mahad An-Nur have done thorough lesson planning by analyzing students' needs, preparing teaching modules, and participating in training related to the implementation of the independent curriculum. Additionally, the teachers at MI Al-Mahad An-Nur have used enjoyable teaching methods in the learning process. Although some challenges were encountered during evaluation, these challenges were overcome, ensuring that the implementation of the independent curriculum in English language learning at MI Al-Mahad An-Nur can run well.